Generation And Characterisation Of RNA Aptamers Against ESAT6 Protein From Mycobacterium Tuberculosis - Bukari, Bakhtiar Affendi (2017)
Aptamers are chemical ligands made up of short nucleotides sequences that are able to bind to target proteins with high affinity and specificity. They are generated using a process called Systemic Evolution of Ligands via Exponential Enrichment (SELEX). Due to their chemical stability and high specificity against the target, aptamers have the potential to become very useful biological tools. The 6 kDa Early Secretory Antigenic Target, or ESAT6, is a secretory protein produced by Mycobacterium tuberculosis and is thought to be a major player in mycobacterial pathogenesis.